Avaliação de um texto de apoio para abordar a Equação de Schörodinger e os orbitais atômicos de átomos hidrogenóides num curso de formação de professores de física - Laitharth, Bernardo Luís Maito (2023)
This dissertation describes a study that sought to analyze the possible contributions of a supporting text on the topic: the applications of the Schrödinger Equation, in the study of atomic orbitals, for the initial training of Physics teachers, in the discipline of Quantum Mechanics. The supporting text prepared, as an educational product that accompanies the dissertation, presents theoretical discussions constructed using, as an organizational reference, Didactic Transposition from Chevallard's perspective. These theoretical discussions are accompanied by reflections on the learning process, particularly cognitive psychology, which are presented in the dissertation, as a way of supporting the study developed. The main objective of the educational product is to provide theoretical and methodological support on the study of the Schrödinger Equation to Physics teachers in initial training. In this sense, the present work is based on the understanding of the need for this content to have greater emphasis in Physics teacher training courses, in order to expand its conceptual domain. The application of the product took place in five meetings, always preparing classes following constructivist ideas, mainly those of Ausubel, totaling 20 hours/class, together with a class from a Physics Degree course, at the University of Passo, located in interior of Rio Grande do Sul, in the Quantum Mechanics curricular component. As a way of validating the teaching material developed, two instruments were established: questionnaires (pre- and post-test) and records in the researcher's logbook. The data collected was structured in order to analyze the students' acceptance of the material prepared, as well as the impact it had on their training. The research appears to have been a success, with the majority of students demonstrating interest and acceptance in the subject and the material used. The practical and expository classes were considered useful and the final act of visualization and interaction with the orbitals helped to consolidate knowledge. Some student difficulties were identified, but were overcome throughout the research. The research is considered valid, based on the positive evaluations of the pre- and post-test questionnaires and the descriptions of the meetings in the logbook. The results also suggest that the supporting text can be used independently, without the need for external materials.